Extracellular multi-unit recording from the olfactory nerve of teleosts - Hubbard, Peter (2021)
Recent studies have shown that ocean acidification affects olfactory-driven behavior in fish. This may be due in part to a reduction in olfactory sensitivity in high PCO2/low pH water. To assess the effects of ocean acidification, or olfactory sensitivity in marine fish in general, we propose that extracellular multi-unit recording from the olfactory nerve is the method of choice. Although invasive, it is sensitive, robust, reproducible and independent of external salinity (unlike the electro-olfactogram [EOG], for example). Furthermore, it records a primary sensory input into the CNS, prior to any central processing. We show that this method can show a reduction in olfactory sensitivity that is both temporary and odorant-dependent, using a range of amino acids to construct concentration-response curves and calculate the thresholds of detection.